Effect of Endophytic Trichoderma sp. Strains on the Agronomic Characteristics of Ecotypes of Theobroma cacao L. under Nursery Conditions in Peru - Antony Chavez-Jalk; Santos Leiva; Leidy G. Bobadilla; Carmen N. Vigo; Marielita Arce; Manuel Oliva-Cruz (International Journal of Agronomy)
Peru is one of the main producers of fine aroma native cacao, expanding its areas considerably in recent years, which makes it necessary to seek adequate management alternatives to obtain advantageous yields. The present work had the objective of testing the influence of Trichoderma sp. endophytic strains on the agronomic characteristics of ecotypes of Theobroma cacao L. under nursery conditions, Cajaruro district, Utcubamba, Amazonas, Peru. The Trichoderma strains evaluated were Trichoderma breve; T. harzianum; T. longibrachatum; T. afrojarzianum, and Trichoderma sp. which were inoculated on cocoa seedlings of ecotypes CCN51; TCHS565; and Nativo fino de aroma. The variables evaluated were chlorophyll indices (at 30, 45, 60, and 70 days after planting), percentage of endophyte colonization, root hair development, trichomes on stems, and agronomic characteristics (plant height, number of leaves, stem diameter, root dry and fresh weight, root size, etc.). The results showed that the application of Trichoderma breve in the fine aroma native cocoa ecotype (T12) presented the highest chlorophyll index at 75 days after planting (DAP) with 43.53 ± 1.59 and 49.77 ± 2.42 for the apex and leaf base, respectively, with a percentage of colonization in the root hairs of 66.67%, and with better characteristics for the number of leaves with 12.00 ± 3.46. T12 showed positive influences for plant height, leaf number, and chlorophyll index. Treatments based on T. harzianum + CCN51 (T5) and T. afroharzianum + TSHS565 (T6) showed 100% colonization of the root hairs and trichomes on stems. Endophytic Trichoderma fungi are an alternative for organic production of fine aroma cocoa in Peru, improving the agronomic characteristics of the crop.